1999
DOI: 10.1042/cs19980070
|View full text |Cite
|
Sign up to set email alerts
|

Increased plasma levels of adrenomedullin in patients with pulmonary hypertension

Abstract: Adrenomedullin, a potent hypotensive peptide, reduces blood pressure and pulmonary vascular resistance, and increases pulmonary blood flow. The mRNA for adrenomedullin and its receptor is highly expressed in the lung, suggesting a regulatory role for adrenomedullin in the pulmonary circulation. To investigate the clinical significance of adrenomedullin in patients with pulmonary hypertension, we studied the relationship between plasma levels of adrenomedullin and pulmonary haemodynamics. Venous, arterial and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…2 AM functions as a local autocrine/paracrine mediator, 3 as well as a circulating hormone, 4 exerting natriuretic, 5 antioxidative, 6,7 and other effects. AM levels in the blood are increased in hypertension, 4,8 heart failure, 9 and myocardial infarction, 10 which suggests its involvement in cardiovascular disease. Homozygotic AM knockout (AM −/− ) mice were dead in utero because of abnormal cardiovascular development.…”
mentioning
confidence: 99%
“…2 AM functions as a local autocrine/paracrine mediator, 3 as well as a circulating hormone, 4 exerting natriuretic, 5 antioxidative, 6,7 and other effects. AM levels in the blood are increased in hypertension, 4,8 heart failure, 9 and myocardial infarction, 10 which suggests its involvement in cardiovascular disease. Homozygotic AM knockout (AM −/− ) mice were dead in utero because of abnormal cardiovascular development.…”
mentioning
confidence: 99%
“…Owji and colleagues reported that there are specific receptors for adrenomedullin in the lungs [Owji et al 1995]. It has been shown that the plasma adrenomedullin concentration increases in proportion to the severity of pulmonary hypertension, and that circulating adrenomedullin is partially metabolized in the lungs [Kakishita et al 1999]. These findings suggest that adrenomedullin plays an important role in the regulation of pulmonary vascular tone.…”
Section: Adrenomedullinmentioning
confidence: 73%
“…216,217 Nagaya and colleagues examined the acute effects of inhaled adrenomedullin in 11 adult patients with idiopathic PH, 218 and adrenomedullin was associated with an acute decrease in PAP and PVR and increase in peak oxygen consumption during exercise.…”
Section: Novel Vasodilatorsmentioning
confidence: 99%